Human immunodeficiency virus type 2 (HIV-2) env gene analysis: prediction of glycoprotein epitopes important for heterotypic neutralization and evidence for three genotype clusters within the HIV-2a subtype - Breuer, Judith; Douglas, Nigel W.; Goldman, Nick; Daniels, Rod S. (Journal of General Virology, 1995)
The env gene sequences of ten tissue-culture-adapted human immunodeficiency virus type 2 (HIV-2) isolates from West African patients were determined. Alignment and comparison of the gene sequences and putative translation products with database sequences revealed 11-29% diversity at the nucleotide level and 15-31% variation at the protein level. From analysis of glycoproteins of HIV-2 strains sensitive and resistant to neutralization by HIV-1 antisera, five regions were identified as putative targets for cross-neutralizing antibody. The HIV-2 equivalent of the HIV-1 V3 loop was not included in this number. However, three of the HIV-2 peptides aligned with regions identified as targets for broad neutralization of HIV-1 strains. These were the V2 and CD4-binding domains of gp120 and the Kennedy domain in gp41. Phylogenetic analysis of the env gene sequences, together with HIV-2 env gene sequences published in the Los Alamos database, support the identification of two distinct HIV-2 subtypes, HIV-2a and HIV-2b. The new sequences are located within the HIV-2a subtype and allow prediction of at least three genotypes, designated I-III. Some correlation of genotype with geographical origin of isolates was noted. Genotype I viruses originate from Guinea Bissau and group II viruses mainly originate from The Gambia. One isolate from Guinea Bissau, HIV-2CAM4, appears phylogenetically older than other viruses in the HIV-2a subtype. The possible implications of this in the light of epidemiological findings in Guinea Bissau are discussed.